A integração da América Latina expressa na educação venezuelana dos governos Chávez: 1999-2009 - Zuck, Débora Villetti (2011)
The study object of this research is to understand how the Latin-America integration category expresses itself on Bolivarian School education in Venezuela, from 1999 to 2009. Aimed to identify and analyze the referred category in the following official documents: Escuelas Bolivarianas and Diseño Curricular del Sistema Educativo Bolivariano, and also, on legal basis, the Ley Orgánica de Educación from 2009. The Latin America integration concept is tied to the history of the Latin-American nation, to the Spanish political independence process and to the historical economic dependence of the region. Two conflicting perspectives face each other in this integrationist process: Bolívar or Monroe. Monroe s triumph categorized the integration as incorporation and submission, and existed during the XIX and XX centuries. After World War II, as a part of the international capitalism recomposition, integration mechanisms emerge, including in Latin-America. ALALC, ALADI, CARICOM, SELA, MERCOSUR, UNASUR, ALBA-TCP are some of the spurious mechanisms in the context of dependent and peripheral capitalism. Even though, at the beginning of the XXI century, Venezuela recovered the Bolivian thinking of the Great Nation. The Bolivarian Revolution, headed by Chavez s governments, puts back, in the regional scenario, the legacy which was considered ―buried‖ until that time. In the legal basis, in the 1999 Constitution, and in the official documents, such as: in the initial government programs, in the PDES and in the PPS, there is a reference to the Latin-American integration. The integration mechanisms which Venezuela is linked to, in different ways ALBA-TCP, UNASUR, MERCOSUR, CELAC and the diplomatic relationships with American dream of life non-adapted countries indicate that the integration, conceived as cooperation, solidarity and complementariness, has been an important tool in the anti-imperialist fight, in the anti-capitalist fight, and in a multipolar world to the XXI century Socialism construction, since 2005. The theoretical-methodological choice of this study allows stating that school education does not have a sovereign character, not even a hegemonic character, considering the social relationships on which education is inserted. From bibliographical, documental and field research, it was possible to perceive that bolivarian school education expresses the Latin-America integration category on philosophical orientations of the curriculum, on the character of Bolivarian Schools, in the objectives and curriculum contents of the Bolivarian Liceo, on the definition of Estado Docente and as one of the main purposes on LOE/2009. This analytical category, on this Organic Law, acquires a fundamental importance to the ―new man‖ venezuelan constitution that, when established on this Latin-American orientation, will be able to contribute to the XXI century Socialism construction. The Latin-American integration, for Venezuela, is an important diplomatic strategy to this new Socialism diffusion. A new social and educational praxis, which can be Latin-American and also Caribbean, might, from concrete marks of this latitude, from the history of Latin-American nations, from the battles fought so far, strengthen a genuine revolution on the ―small humanity‖ terms.